Advances in optical surface figuring by reactive atom plasma (RAP) - Castelli, Marco (Cranfield University, 2012)
In this thesis, the research and development of a novel rapid figuring procedure for large ultra-precise optics by Reactive Atom Plasma technology is reported. The hypothesis proved in this research is that a metre scale surface with a form accuracy of ~1 μm PV can be figure corrected to 20 – 30 nm RMS in ten hours. This reduces the processing time by a factor ten with respect to state-of-the-art techniques like Ion Beam Figuring. The need for large scale ultra-precise optics has seen enormous growth in the last decade due to large scale international research programmes. A bottleneck in production is seen in the final figure correction stage. State-of-the-art processes capable of compliance with requisites of form accuracy of one part in 108 (CNC polishing, Magneto-Rheological Finishing and Ion Beam Figuring) have failed to meet the time and cost frame targets of the new optics market. Reactive Atom Plasma (RAP) is a means of plasma chemical etching that makes use of a Radio Frequency Inductively Coupled Plasma (ICP) torch operating at atmospheric pressure. It constitutes an ideal figuring alternative, combining the advantages of a non-contact tool with very high material removal rates and nanometre level repeatability. Despite the rapid figuring potential of this process, research preceding the work presented in this manuscript had made little progress towards design and implementation of a procedure for metre-class optics. The experimental work performed in this PhD project was conducted on Helios 1200, a unique large-scale RAP figuring facility at Cranfield University. Characterisation experiments were carried out on ULE and fused silica surfaces to determine optimum process parameters. Here, the influence of power, surface distance, tool speed and surface temperature was investigated. Subsequently, raster-scanning tests were performed to build an understanding on spaced multiple passes ... [cont.].
Keywords: Figure correction; tool-path algorithms; large-scale; ultra-precise surfaces; rapid processing times